The Dawn of Digital Payments: Revolutionizing India's Financial Landscape - Showkat Ahmad Dar, (LC International Journal of STEM (ISSN: 2708-7123), 2023)
The study investigates how India's digital payments revolution has altered the financial landscape. India has recently seen a huge movement towards digital payments as a result of the quick development of technology and the widespread usage of cell phones. This transformation has significantly changed the financial landscape of the country along with how people interact. Demonetization, a government program that was put into effect in 2016, made a substantial contribution to the growth of electronic payments. People and businesses started looking for other payment options as a result of the abrupt withdrawal of high-value currency notes, which increased the volume of digital transactions. People are finding it easier and easier to access digital payment systems as a result of the widespread use of smartphones and the affordability of internet access. With the rise in popularity of mobile payment apps like Paytm, PhonePe, and Google Pay, India's financial landscape has changed. Financial inclusion enabled by the digital revolution has allowed millions of unbanked and underbanked individuals to access formal financial services through digital payments. With just a smartphone and a bank account, people can easily send money, pay bills, and shop online. This change has promoted economic openness in the country and empowered small businesses.